Application of vagal-mediated heart rate variability and subjective markers to optimise training prescription: An Olympic athlete case report - Chiron, F.; Bennett, S.; Thomas, C.; Hanon, C.; Léger, D.; Lopes, P. (International Journal of Disabilities Sports and Health Sciences, 2024)
Purpose: The aim of this case study was to investigate whether the variation in parasympathetic branch activity, in conjunction with subjective data, could optimize the training prescription for an elite athlete during an Olympic season. Methods: During the preparatory phase for the Tokyo Olympic Games, a world-class female 3000m steeplechase runner (Age: 20 years, Height: 168 cm, Weight: 52 kg, VO2max: 67.1 mL·min·kg-1) recorded Heart Rate Variability (HRV), conducted orthostatic tests, and completed subjective evaluations four times a week throughout the different training periods that constitute a pre-Olympic season. The Pearson correlation coefficient and the Shapiro-Wilk test, along with paired T-tests, were used to assess correlations and compare mean differences between variables concerning baseline measurements and each of the other training periods. Results: The natural logarithm of the root mean square of the standard deviation during supine measurement (LnRMSSDsu) exhibited a significant negative correlation with the training load based on Rating of Perceived Exertion (RPE) and sleep quality (P < 0.05). Heart rate during supine measurement (HRsu) showed a significant positive correlation with subjective perceived exertion, sleep quality, stress, muscle soreness, and fatigue (P < 0.01). Compared to the baseline (rest), LnRMSSDsu, HRsu, RPE, and sleep quality were significantly different during the training, camp, and altitude training camp periods. Conversely, markers of standing Heart Rate Variability (HRV) did not differ during competition periods. Conclusion: Standing Heart Rate Variability, when combined with subjective markers, serves as a relevant monitoring tool for adapting training periods to regulate psychophysiological effects.